An investigation of the effects of critical infrastructure on urban mobility in the city of Medellín. (2015) - Jaller, Miguel; GonzÁ¡lez-Calderón, Carlos A.; Yushimito, Wilfredo F.; SÁ¡nchez-Díaz, IvÁ¡n D.
Critical infrastructure refers to the type of facilities, services, and installations (e.g., transportation, communication, energy systems) that are essential for the functioning of a community, city or country. This paper describes the findings of the research conducted to identify the transportation network critical facilities (road links) and their impacts on urban mobility for the city of Medellin, the second largest city in Colombia. This paper analyses the negative effects on travel time when a facility is disrupted or the capacity is suddenly reduced (e.g., accident, natural or manmade disaster, dedicated bike-route, maintenance, and construction). Criticality is identified following two methodologies: 1) comparing the travel time of the network users solving the user equilibrium (UE) traffic assignment problem between the base case and the disrupted network; 2) assessing the impact of the disrupted facility on the path travel times between affected origin-destinations zones.